Upala: Historical Reconstruction of its Landscape by Ancient Settlements - Peters Solórzano, Gertrud (Revista de historia., 2018)
This article aims the diverse landscape of Upala in the first half of the century, which was developed by the settlers of that place. For that reason, this research incorporates pieces of the autobiographies of the farmers, both Costa Ricans and Nicaraguans, who describe the history of the space environment. Furthermore, factors, such as the physical geography, social environment and cultural background, are characteristics considered to study the historical landscape as a whole. Moreover, the reader can appreciate a detailed analysis of four aspects: 1) the settlements and the use of natural resources; 2) Upala’s first agriculture production; 3) the migration and social relations patterns of Costa Ricans and Nicaraguans and; 4) the regional identity of this population.